2000
DOI: 10.1007/s004030000173
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HSP70 prevents ultraviolet B-induced apoptosis of a human melanoma cell line

Abstract: The heat shock response is a highly conserved reaction common to all cells and organisms. It has been reported that hyperthermic treatment can induce the expression of the heat shock protein (HSP) and can protect cells from ultraviolet (UV) B radiation. In this study, we evaluated the effects of induced HSP70 on resistance to UV radiation. G361 amelanotic human melanoma cells were irradiated with increasing doses of UVB. UVB irradiation caused apoptotic cell death in these cells. Following transfection with MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In melanoma, Hsp70 was shown to be upregulated in a subset of primary tumors and cell lines (Dressel et al, 1998;Ricaniadis et al, 2001). The extent to which Hsp70 contributes to melanoma chemoresistance in vivo is unknown, but melanoma cells overexpressing Hsp70 have a higher resistance to UV irradiation (Park et al, 2000).…”
Section: Caspase-independent Cell Deathmentioning
confidence: 99%
“…In melanoma, Hsp70 was shown to be upregulated in a subset of primary tumors and cell lines (Dressel et al, 1998;Ricaniadis et al, 2001). The extent to which Hsp70 contributes to melanoma chemoresistance in vivo is unknown, but melanoma cells overexpressing Hsp70 have a higher resistance to UV irradiation (Park et al, 2000).…”
Section: Caspase-independent Cell Deathmentioning
confidence: 99%
“…104,105 These two heat-shock proteins are both able to inhibit the apoptosome formation, 106,107 and hsp70 can also antagonize the proapoptotic effects of apoptosis-inducing factor. 108 Overexpression of hsp70 can prevent UVB-induced apoptosis in an epidermal carcinoma line, 109 and hsp70-deficient mice are more susceptible to UVB-induced apoptosis. 110 Taken together, these observations may reflect the presence of strong antiapoptotic mechanisms, which may protect keratinocytes from environmental stress-induced apoptosis.…”
Section: Mitochondrial Factors and Apoptosome Formationmentioning
confidence: 99%
“…14 In fact, different HSPs can interfere with both anti-and proapoptotic pathways (reviewed in Beere 8 and Sreedhar and Csermely 9 ). Numerous studies, however, have shown that overexpression of HSP70, in either transgenic mice or transfected cells, can protect different somatic cells from apoptotic death induced not only by the hyperthermia 15 but also by other stimuli, including ischemia, 16 nitric oxide, 17 adriamycin, 18 UV-B radiation 19 or pathogenic viruses. 20 Two members of the HSP family are expressed normally under non-heat shock conditions specifically during spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%